Barriers and facilitators to exercise in people with idiopathic inflammatory myopathies: a qualitative study - Natalie Li; Stephanie Frade; Lucinda Roper; Matthew JS Parker; Peter Youssef; Mandana Nikpour (BMC Rheumatology)
Abstract Background Idiopathic inflammatory myopathies (IIM) are a group of related chronic autoimmune diseases characterized by muscle inflammation and numerous other potential organ specific manifestations. People with IIM often present with reduced muscle strength, endurance, and aerobic capacity, directly impacting physical function and health-related quality of life. With emerging evidence supporting exercise in IIM, we sought to explore the experiences of exercise in people with IIM to further inform person-centered exercise interventions. Methods Semi-structured interviews were conducted with IIM patients attending the rheumatology clinic at Royal Prince Alfred Hospital, Sydney, Australia. Interviews were audio-recorded, transcribed, de-identified using alphanumeric codes, and analyzed thematically. Results Twenty adults (women = 12, men = 8) with a mean age of 52.6 ± 12.9 years and a mean disease duration of 9.5 ± 8.9 years were included. Nine themes emerged: barriers to exercise (5 themes) and facilitators to exercise (4 themes). Barriers to exercise include (1) variability of disease burden (day-to-day symptom fluctuation, episodic flares, and side effects of treatments), (2) spectrum of disease severity, (3) fear of disease exacerbation, (4) navigating logistical conflict and (5) exercise and disease knowledge deficiency (lack of exercise knowledge in people with IIM and lack of disease-specific knowledge in exercise providers). Facilitators to exercise include (6) knowledge empowerment (participant education on the benefits of exercise in IIM to empower exercise engagement, and disease-specific education for exercise providers to facilitate understanding and trust with their patients) (7) improving exercise motivation through physical and mental wellbeing, (8) promoting positive affect to improve exercise engagement and adherence (social involvement and distractions), and (9) individualizing exercise to clinical and social circumstances. Conclusions People with IIM experience several barriers to exercise including disease severity, symptom unpredictability, fear of disease exacerbation, and difficulty scheduling exercise around medical appointments and life commitments. Education about the role of exercise and individualising exercise for people with IIM are central to improving exercise engagement and confidence. It is also important for health care providers to support people with IIM in making the link between physical and mental well-being and maintenance of independence and quality of life.